2012
DOI: 10.1002/jnr.23128
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of human mesenchymal and hematopoietic stem cells on rotenone‐treated parkinsonian mice

Abstract: To appreciate the potential applications of stem cell technology in neurodegenerative diseases, including Parkinson's disease (PD), it is important to understand the characteristics of the various types of stem cells. In this study, we designed a set of experiments to compare the ability of three types of human stem cells--mesenchymal stem cells (MSCs), bone marrow CD34(+) cells (BM), and cord blood CD34(+) cells (CB)--using rotenone-treated NOD/SCID mice. Rotenone was orally administered once daily at a dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Recent experimental studies showed that MSC are more efficient at modulating the neural microenvironment by promoting growth factor release and glial activation, mainly of oligodendrocytes, which enables better structural and functional reorganization compared with hematopoietic stem cells used in this study. 96,97 This observation is supported by articles included in this review, which, besides confirming the ischemic region reduction after 7 days after stem cells' administration in both photothrombosis and temporary occlusion of the middle cerebral artery model, also showed an improvement in memory behavioral tests, such as the Morris water maze, and adapted neurological scales.…”
supporting
confidence: 74%
“…Recent experimental studies showed that MSC are more efficient at modulating the neural microenvironment by promoting growth factor release and glial activation, mainly of oligodendrocytes, which enables better structural and functional reorganization compared with hematopoietic stem cells used in this study. 96,97 This observation is supported by articles included in this review, which, besides confirming the ischemic region reduction after 7 days after stem cells' administration in both photothrombosis and temporary occlusion of the middle cerebral artery model, also showed an improvement in memory behavioral tests, such as the Morris water maze, and adapted neurological scales.…”
supporting
confidence: 74%
“…Our group http://dx.doi.org/10.1016/j.neulet.2014. 10.039 0304-3940/© 2014 Elsevier Ireland Ltd. All rights reserved. previously reported the beneficial effects of intravenous delivery of human bone marrow-derived mesenchymal stem cells (hBMMSCs) into rotenone-treated mice [10].…”
Section: Introductionmentioning
confidence: 95%
“…The results of some studies suggest that the direction of differentiation depends on the nature of evolving pathology and cell microenvironment [15]. For instance, MMSC transplanted into the striatum had a positive effect on the course of Parkinson's disease due to improvement of the trophic function and differentiation into cells with tyrosinase activity [10,19] typical of dopaminergic neurons that are defi cient in Parkinson's disease. In our model of AD, MMSC differentiation into astrocytes is probably dictated by the necessity to maintain neuronal survival via stimulation of phagocytic activity of astrocytes involved into elimination of growing β-amyloid deposits inducing neuronal death [21].…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous MMSC are precursors of 10% microglial cells that are very important in AD because they can eliminate amyloid deposits. It should be noted that MMSC, like other stem cells, are characterized by tropism to areas of pathology, where they differentiate into cells of damaged tissue, thereby contributing to functional recovery [10,19]; therefore, it was interesting to study differentiation of MMSC migrating across the blood-brain barrier into the brain of OBE mice.…”
Section: Resultsmentioning
confidence: 99%